UK arms exports during 2016 : Government Response to the Committees' First Joint Report : First Joint Special Report of Session 2017-19 : Fourteenth Special Report of the Defence Committee, Eighteenth Special Report of the Foreign Affairs Committee, Ninth Special Report of the International Development Committee and Fifth Special Report of the International Trade Committee /: Government Response to the Committees' First Joint Report : First Joint Special Report of Session 2017-19 : Fourteenth Special Report of the Defence Committee, Eighteenth Special Report of the Foreign Affairs Committee, Ninth Special Report of the International Development Committee and Fifth Special Report of the International Trade Committee. ([2018-11-29]) - Unknown
No abstract available